A comparative study of anthropometric measurements and body composition between junior football and basketball players from the Serbian National League - DUSKO BJELICA; BOJAN MASANOVIC; DRAGAN KRIVOKAPIC (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: ‪The purpose of this study was to describe anthropometric characteristics and body composition of junior football and basketball players as well as to make comparisons between them. Material and methods: ‪In this study 70 males were enrolled, divided into three groups: 25 football players, 13 basketball players and 32 healthy sedentary subjects. All subjects were assessed for the anthropometric measures required to calculate body composition variables, using the standardized procedures. Descriptive statistics were expressed as a mean (SD) for each variable. To detect the effects of each type of sport ANOVA and LSD Post Hoc tests were carried out. Results: ‪The results showed there was no significant difference in the body mass index and bone content in the body among the groups, while a significant difference was found for body height and body weight as well as for the other two body content variables measured (muscle and fat) among the groups. Conclusions: ‪These findings may give coaches from the region better working knowledge and advise them to follow recent selection process methods to be more successful during talent identification.